2017
DOI: 10.1039/c7ra00396j
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oil type on network formation by protein aggregates into oleogels

Abstract: The aim of this study was to assess the effect of oil type on the network formation of heat-set protein aggregates in liquid oil. The gelling properties of such aggregates to structure oil into so-called 'oleogels' are related to both the particle-particle and particle-solvent interactions. To change these interactions, four different oils (medium chain triglyceride oil, sunflower oil, extra virgin olive oil and castor oil) differing in polarity were used. The rheological properties of the protein aggregate ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 39 publications
1
43
0
2
Order By: Relevance
“…The influence of pH will lead to different properties of the aggregates, such as exposed hydrophobicity and stabilization through disulfide bonds. Such aggregates can be used to stabilize foams [ 18 ] and emulsions [ 19 ] or as oil-structuring agents [ 20 ]. Furthermore, aggregates are considered the building block of protein gels.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of pH will lead to different properties of the aggregates, such as exposed hydrophobicity and stabilization through disulfide bonds. Such aggregates can be used to stabilize foams [ 18 ] and emulsions [ 19 ] or as oil-structuring agents [ 20 ]. Furthermore, aggregates are considered the building block of protein gels.…”
Section: Introductionmentioning
confidence: 99%
“…The most common limitations of the EC oleogels are the poor oxidative stability because of the high temperatures (>135-140 • C) required to induce the polymer EC gelation (Gravelle et al, 2012). Therefore, using hydrocolloid-based oleogelators including different sources of proteins (Patel et al, 2015;de Vries et al, 2017) and polysaccharides like celluloses ethers, methylcellulose (MC) (Patel et al, 2014a;Tanti et al, 2016a,b;Meng et al, 2018a), and hydroxypropylmethylcellulose (HPMC) (Patel et al, 2013;Oh and Lee, 2018;Oh et al, 2019;Bascuas et al, 2020), have attracted noticeable research attention. Hydrocolloids are widely used in food because of their commercial availability, large production, and low cost (Scholten, 2019;Abdolmaleki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Different correlations have been observed between the oil polarity and strength of the gel, depending on the gelling agent used. De Vries et al () reported that the gel strength of the network, formed by proteins aggregates, was affected by the polarity of the oil, resulting in weaker oleogels when using a more polar oil. However, Gravelle et al () attributed the increase in mechanical strength of the oleogel to an increase in the polarity of the oils using ethylcellulose as gelling agent.…”
Section: Resultsmentioning
confidence: 99%